2013
DOI: 10.1111/agec.12025
|View full text |Cite
|
Sign up to set email alerts
|

Managing basis risk with multiscale index insurance

Abstract: Agricultural index insurance indemnifies a farmer against losses based on an index that is correlated with, but not identical to, her or his individual outcomes. In practice, the level of correlation may be modest, exposing insured farmers to residual, basis risk. In this article, we study the impact of basis risk on the demand for index insurance under risk and compound risk aversion. We simulate the impact of basis risk on the demand for index insurance by Malian cotton farmers using data from field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 16 publications
2
127
0
2
Order By: Relevance
“…Of particular concern in this paper, most index insurance policy holders face some remaining basis risk. This has two potential sources: design risk due to differences between the index and the actual covariate risk it is meant to mimic, and idiosyncratic risk resulting from heterogeneity among individuals' losses within the same index region (Elabed et al 2013).…”
Section: Basis Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern in this paper, most index insurance policy holders face some remaining basis risk. This has two potential sources: design risk due to differences between the index and the actual covariate risk it is meant to mimic, and idiosyncratic risk resulting from heterogeneity among individuals' losses within the same index region (Elabed et al 2013).…”
Section: Basis Riskmentioning
confidence: 99%
“…Other papers have used simulations, aggregate-level data, and/or experiments to examine basis risk (e.g., Breustedt, Bokusheva & Heidelback 2008;Dercon et al 2014;Elabed et al 2013;Leblois, Quirion & Sultan 2014;Norton, Turvey & Osgood 2012). Again, basis risk is consistently identified as a key factor in product quality and uptake, but little or nothing can be said about the relative magnitude or distribution of basis risk among households.…”
Section: Introductionmentioning
confidence: 99%
“…Norton et al (2012) quantified and developed concepts on how to price spatial basis risk for WII. Elabed et al (2013) analyzed a multi-scale index insurance contract to reduce basis risk. Other studies concentrated on the role of government and suggested that the government should not only establish an appropriate legal and regulatory framework (Barnett and Mahul 2007) but also provide more subsidies to crop insurance (Clarke et al 2012;Skees 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finding practical and reasonable indices that can capture weather fluctuations and be strongly correlated with crop yield losses is necessary and critically important for improving crop insurance operation (Stoppa and Hess 2003;Barnett and Mahul 2007;Elabed et al 2013). Therefore, the present study focused on the following objectives: (1) to determine which temperature-based index could potentially be used at the county scale; (2) to characterize the spatial pattern of insurable counties and spatial relationship between different groups of insurable counties; and (3) to analyze correlation coefficients of insurable counties at different spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The color represents frequency at which rainfall intensity and frequency fall into a given range, based on 80 years of historical data at Belleville, KS. Designing the strike level and payoff function following the RIF-driven yield contour (red line) will eliminate the unnecessary tradeoff between basis risk and strike frequency captured in Figure 4b. among farmers, the first challenge lies in reducing BR (Carter et al, 2014;Elabed et al, 2013;Elabed & Carter, 2015;Jensen & Barrett, 2016;Miranda & Farrin, 2012). The low correspondence between weather indexes and crop damages has prompted the use of alternative indexes such as ET, normalized difference vegetation index (NDVI), and soil moisture.…”
Section: Discussionmentioning
confidence: 99%